Buckling analysis of laminated composite and sandwich beams by the finite element method. (15th April 2016) - Kahya, Volkan
Abstract: Buckling of laminated composite beams is studied by the finite element method. A multilayered beam element presented here consists of N -layers, and includes totally 3 N  + 7 degrees of freedom (DOFs). Delamination and slip between the layers are avoided. Effect of shear deformation is considered according to the first-order shear deformation theory (FSDT). Numerical results for buckling loads of laminated beams with different boundary conditions and lamina stacking are presented. Comparisons show that results obtained agree well with those of previous works available in the literature.